Evaluation of a magnetic activated charcoal modified with non-ionic silicone surfactant as a new magnetic solid phase extraction sorbent with triazine herbicides as model compounds in selected milk and rice samples - Mohd, Noraini; Gopal, K.; Raoov, Muggundha; Mohamad, Sharifah; Yahaya, Noorfatimah; Lim, V.; Zain, Nur Nadhirah Mohamad (Elsevier, 2019)
The non-ionic silicone surfactant (OFX 0309) has been applied in cloud point extraction for the extraction of triazine herbicides in food samples. Evidence has shown that the non-ionic silicone surfactant demonstrated a good performance as an extractor toward triazine herbicides. In this present study, OFX 0309 surfactant was combined with activated charcoal (AC) due to their valuable properties. Activated charcoal modified with non-ionic silicone surfactant coated with magnetic nanoparticles (AC–OFX MNPs) was synthesized and characterized by FT-IR, VSM, SEM, TEM and BET. This novel material was applied as a magnetic adsorbent for the pre-concentration and separation of triazine herbicides due to hydrophobic interaction between polysiloxane polyether of OFX 0309 surfactant and triazine herbicides. Under optimal conditions, the proposed magnetic solid phase extraction method using AC-OFX MNPs adsorbent was applied to extract triazine herbicides from selected milk and rice samples using high performance liquid chromatography coupled with diode array detector. The validation method revealed a good linearity (1 – 500 μg L–1) with the coefficient of determination (R2) in the range of 0.992–0.998 for the samples. The limits of detection (LOD) of the developed method were 0.04 – 0.05 µg L–1 (milk sample) and 0.02 – 0.05 µg L–1 (rice sample). The limits of quantification (LOQ) were 0.134 – 0.176 µg L–1 (milk sample) and 0.075 – 0.159 µg L–1 (rice sample). The recoveries of the triazine compounds ranged from 81% to 109% in spiked milk samples and from 81% to 111% in spiked rice samples, with relative standard deviations (RSD) values lower than 13.5% and 12.1% for milk and rice samples, respectively. To the best of our knowledge, this is the first study that have investigated the use of magnetic nanoparticles coated activated charcoal modified with OFX 0309 surfactant for pretreatment of triazine herbicides in food samples analysis for simultaneous separation of organic pollutants.